HAKEKAT PENDIDIKAN MENURUT PAKAR PENDIDIKAN (Studi tentang Persamaan dan Perbedaan Makna) - St. Aisyah Abbas (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2016)
Substantially is about the journal, "Nature of Education Specialist Education Perspective" which discusses how the nature of education according to Islamic scholars and the West, and how the similarities and differences in the nature of education proposed education experts. Because so the urgency of education for human life, so many experts brainstorm to generate a wide range of scientific work as a form of responsibility in the intellectual life of the nation. According to the western version of that education as a human activity to improve the personality with the potential to foster the personal that is spiritual (mind, intention, taste, creativity and kindness conscience). And physical (the five senses and skills). Meanwhile, according to the Islamic version of education is not only the transfer of knowledge and skills alone, but can form a complete personal integrity that is physical, spiritual and moral. Equation meaning of education between Western and Islamic experts that all lead to efforts to prepare students who do adults to form a pattern of change in the child, so as to achieve perfect ripeness. While the difference is the Western version tends to look on the achievement of cognitive, psychomotor. While the version of Islam that the educational process is not only to achieve cognitive and skill alone, but the most important is the affective form (form of attitudes, moral, spiritual values), thus forming a personality muliah Allah SWT.